Determination of financial factors in the latest theories of economic growth of territorial communities - Halyna Voznyak; Krystyna Patytska; Taras Kloba (Vasyl Stefanyk Precarpathian National University, 2020)
In today's modern circumstances ensuring the economic growth of territorial communities requires theoretical redefining and additional research, since new challenges have negatively affected the well-being of the population and ensuing progress. The purpose of the article is to determine financial factors in the latest theories of economic growth of territorial communities. Scientific approaches to the definition of "territorial community" are generalized, own approach is offered and the main features of territorial community (territorial, natural, social-psychological, historical-cultural, organizational-functional, political, economic) are substantiated. Emphasis is placed on the need for a new theoretical approach to the development of territorial communities based on the synthesis and combination of basic guidelines and principles of modern scientific concepts and models, their interpretation in the context of local development. The latest theories of economic growth are studied, including: the theory of endogenous growth, inclusive development and the theory of sustainable development (E. Ostrom's concept of community resource management is highlighted). It is substantiated that the model of endogenous growth is focused on reducing inequality of economic development through the use of internal factors, mechanisms of management and management of the territory. There are two vectors of achieving inclusive development of territorial communities: internal - maximum involvement of community members in the process of its development; external - ensuring access of members of the territorial community to the opportunities provided by more developed communities. It is emphasized that the key idea in E. Ostrom's research is to achieve efficiency and substantiation of ways of community management of common resources. Within the framework of the theory of inclusive development, a review of the concept of financial inclusion, which raises the issue of community development - "banking deserts". The existence of interdependence of perception of members of territorial communities - "banking deserts" of opportunities and prospects of obtaining banking services is indicated, which requires the involvement of theoretical foundations of behavioral economics in the study of this issue. The factors of economic growth of territorial communities are systematized, which are united into five groups: natural, factors of human development; social, production and financial. The financial factors of economic growth of territorial communities include: budget; investment, inflation, monetary. The expediency of applying the ideas of the latest theories of economic growth in the process of analyzing financial factors is substantiated.